Parenting management in forming social-emotional development of kindergarten in Belitung - Sri Nurhidayah (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2024)
Social emotionality in children is one of the most important things in forming a child's personality. Air Seru State Kindergarten, Belitung Regency has various programs for personality development. The aim of this research is to analyze the conditions of parenting management in improving social emotional development in the Air Seru State Kindergarten, Belitung Regency as well as increasing the role of parents and educators in responding to children's social emotional development. This research uses qualitative research with descriptive analysis methods using data collection techniques, namely observation, interviews and documentation. The informants in this research consisted of institutional managers and parents. To complete the data, namely articles and/or others related to this research. The results of this research show that the parenting management carried out at the Air Seru State Kindergarten, Belitung Regency can shape the social emotionality of students and the closeness between parents, educators and students is well established on a regular basis, this is due to the planning that is carried out such as group community activities. parents and school institutions that run actively, students' social development that develops with direction and training at school and then accompanied by application at home. However, there are weaknesses, namely that some children lack parenting patterns due to problems at home or in the family.